Modeling techniques group setting on increasing adolescent self-regulation in traffic violation prevention - Nurfarhanah Nurfarhanah; Rezki Hariko; Firman Firman; Zikry Latupasjana Ersya; Maya Mashita Rachmi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
Traffic accidents are the leading cause of death among young people aged 15–29. This study aims to reveal the efficiency of group setting modeling techniques to improve self-regulation in preventing traffic violations in adolescents. There are two groups of students in SMK 1 Padang City. The group consists of 25 students. This type of experimental research with Quasy-Experiment design. The research sample is Vocational High School (SMK) students. Sampling using random cluster sampling. The instrument used is a self-regulation questionnaire in traffic. Then analyzed using the Wilcoxon Signed Ranks test and the Kolmogorov-Smirnov Two Independent sample with the help of the Statistical Product and Service Solution (SPSS) version 22 program.This study found that adolescent self-regulation in traffic increased after being given counseling services using group setting modeling techniques. This research can be used to reduce the level of traffic violations on the highway, especially among teenagers, especially in the city of Padang. The average score of group members in the pretest was 73.8 while the posttest was 91.72, meaning that there was an increase in the score of 13.00. The provision of group setting modeling techniques can significantly improve adolescent self-regulation against traffic violations.  This research can be an alternative in the world of education to prevent traffic violations, especially in adolescents.